Systematic Literature Review: The Role of Insurance The journey of Sharia in Increase Protection Muslim Tourists - Marshanda Ridia Amelia; Taufiqur Rahman (AL-ARBAH: Journal of Islamic Finance and Banking, 2025)
Purpose - This article aims to examine and analyze the role of Islamic travel insurance in improving protection for Muslim tourists. Specifically, this study focuses on understanding the mechanism of Islamic insurance, as well as the extent to which this insurance is able to answer the needs and challenges of Muslim travelers in the context of halal travel.. Method - In this study, data search was conducted using the Systematic Literature Review (SLR) Method by summarizing findings from previous studies that are relevant to the research topic. The keywords from Indonesian used to search for data for this study are "Sharia Travel Insurance" and "Protection for Muslim Tourists". Result - Islamic travel insurance, based on the principle of takaful, provides protection for Muslim travelers through sharia-compliant mechanisms, such as tabarru and wakalah bil ujrah contracts. However, travelers still face various obstacles, such as a lack of understanding of takaful, limited coverage, and constraints in regulations and claim procedures. They need insurance coverage that covers important aspects, such as legal certainty that is free from gharar, maysir, and usury, as well as access to halal food and prayer facilities during the trip. Case studies reveal that defaults in Islamic travel insurance claims for Umrah pilgrims often occur due to a lack of transparency in the claim procedure. To increase traveler confidence, the insurance industry needs to design more inclusive products, improve regulations that support sharia compliance, and improve financial literacy so that protection for Muslim travelers is more optimal. Implication - This study used data from Google Scholar to identify related articles, with a total of 1,010 articles found in the initial stage. After a screening process based on the relevant year range, 270 articles were identified from journals published in the period 2020–2025 as the basis for initial selection. Further screening was carried out using the Open Refine application by considering the inclusion criteria that had been set. From the results of this process, 27 articles were obtained that were relevant to the research topic, with 8 of them having a high level of relevance to the research title. Originality - This study examines the mechanism of Islamic travel insurance and its role in meeting the needs and overcoming the challenges of Muslim travelers in halal travel. The discussion covers fundamental aspects, coverage, as well as regulatory barriers and claim procedures. In addition, this study evaluates innovative strategies in product development and increasing understanding of Islamic finance to ensure more effective protection for Muslim travelers. Keywords:                     Sharia Insurance, Insurance Sharia Travel, Protection Muslim Tourists.